Safe within - Page, Jean Reynolds (New York : William Morrow, 2012)
Returning to her childhood home in Lowfield, North Carolina, so that her husband can live out his final days in his favorite place, Elaine Forsythe gets more than she bargains for when her husband's mother, who hasn't spoken to her in 25 years, arrives and stirs up trouble.
Keywords: Mothers-in-law -- Fiction; Families -- Fiction